The Capital of the Urals: Yekaterinburg’s Administrative Status and Citizens’ Identity Evolution between the 18th – Early 20th Century - Ol'ga Sergeyevna Porshneva; Elena Yuryevna Kazakova-Apkarimova (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2015)
The article aims to analyze the connection between the evolution of Yekaterinburg’s administrative status and that of its citizens’ identity between the 18th – early 20th century. With reference to historical and historiographic sources, the authors demonstrate that Yekaterinburg, while being a capital and a European city in many respects, was a dynamically developing place with advanced commerce and industry, science and culture in the period in question. The authors conclude that the myth of the capital character of Yekaterinburg that is an integral part of the citizens’ mentality has a long-standing history and express an opinion that Yekaterinburg’s capital identity as a macro-region was closely connected to the growth of regional self-consciousness in history.